Bohemian Bolsheviks : Dispatches from the Culture and History of the Left - Wald, Alan M., (Historical Materialism Book Series ;, 2025)
The rubric, 'Bohemian Bolsheviks,' captures Alan Wald's sustained fascination with persistent contradictions between the image of Left political commitment and the actuality of experience, especially in relation to cultural work and cultural workers. Marxist political alignment engages a welter of intimate and biographical factors enriching the record of a varied history of fiction, poetry, literary criticism, and other intellectual practices. Exploring a field of study marked by enduring paradoxes of modernity, this volume is a sharp reminder that historical narrative not only shapes our sense of the terrain under our feet-but also the horizon in front of us.